Analisis Keberlanjutan Pembangunan Kota Tepian Pantai (Studi Kasus: Kota Baubau Provinsi Sulawesi Tenggara) - Suparman Supardi; Sigid Hariyadi; Achmad Fahrudin (Jurnal Wilayah dan Lingkungan, 2017)
The complexity of coastal development in Baubau City needs to be anticipated carefully for hindering coastal ecosystems sustainability away from disruptions and threats. Environmental degradation resulted from developments could be disastrous to economic and infrastructure sectors as well as human lives. Therefore, development initiatives are supposed to comply with the principles of sustainable development. Accordingly, sustainability analysis is necessary to figure out the sustainability status of Baubau City development. The purpose of this study is to analyze the sustainability of Baubau City development in accordance with multidimensional measurement of ecological, economic, social, infrastructure and technology, and law and institution. The data used in this study include primary and secondary data obtained through literature studies, expert discussions/stakeholder, interviews, questionnaires, and field surveys. The sustainability analysis applies multidimensional scaling, leverage, Pareto, and Monte Carlo techniques. The results show that Baubau City is quite sustainable in technological infrastructure dimension (74,77), and institutional law dimension (65,87), but less sustainable in ecology dimension (32,90) and economic dimension (41,87), and unsustainable in social dimension (20,61). In addition, there are 35 sensitive attributes affecting the sustainability of Baubau City development.